Effects on physiologic measures of appetite from intragastric balloon and endoscopic sleeve gastroplasty: results of a prospective study - Rapaka, Babusai; Maselli, Daniel B.; Lopez-Nava, Gontrand; Bautista-Castaño, Inmaculada; Matar, Reem; Jaruvongvanich, Veeravich; Vargas, Eric J.; Storm, Andrew C.; Acosta, Andres; Abu Dayyeh, Barham K. (Chinese medical journal, 2022)
Background:Endoscopic bariatric therapies can help address widening management gaps in obesity. Their ability to facilitate weight loss is largely tied to influences on appetite through perturbations of gastric emptying and accommodation. As these tools gain traction in obesity therapy, their physiologic underpinnings require exploration, which may enhance efficacy, tolerance, and patient-tailored care.Methods:We prospectively assessed consecutive subjects with fluid-filled intragastric balloons (IGBs) (n = 18) placed between October 2016 and June 2017 or underwent endoscopic sleeve gastroplasty (ESG) (n = 23) from March 2018 to June 2018. Patients underwent physiologic appraisal at 3 months with 13C-spirulina-based gastric emptying breath test to determine time to half emptying (T50), as well as maximum tolerated volume (MTV) of a standard nutrient drink test. Changes in T50 and MTV at 3 months were compared with percent total body weight loss (%TBWL) at 3 and 6 months using best-fit linear regression.Results:The change in T50 at 3 months correlated with %TBWL at 3 months for IGB (P = 0.01) and ESG (P = 0.01) but with greater impact on %TBWL in IGB compared to ESG (R2 = 0.42 vs. 0.26). Change in T50 at 3 months was predictive of weight loss at 6 months for IGB (P = 0.01) but not ESG (P = 0.11). ESG was associated with greater decrease in MTV compared to IGB (340.25 ± 297.97 mL vs. 183.00 ± 217.13 mL, P = 0.08), indicting an enhanced effect on satiation through decreased gastric accommodation. Changes in MTV at 3 months did not correlate with %TBWL for either IGB (P = 0.26) or ESG (P = 0.49) but trended toward significance for predicting %TBWL at 6 months for ESG (P = 0.06) but not IGB (P = 0.19).Conclusion:IGB and ESG both induce weight loss but likely through distinct gastric motor function phenotypes, and gastric emptying may predict future weight loss in patients with IGB.